Studying the anticipator of satisfaction in male customers of fitness centers - Mehdi Talebpour; Mojtaba Rajabı; Mohamad Ali Sahebkaran; Mohammad Mosalanejad (Türk Spor ve Egzersiz Dergisi)
The purpose of current study is to study anticipators of satisfaction in male customers of fitness centers in Shahrood city. The population for this study is7560 male customers in Shahrood city 408 of which were chosen randomly as the sample. Three self-made questionnaires made by the researcher himself. Cronbach's alpha was determined for those three questionnaires, by experts, as 0.90, 0.88, and 0.78 respectively. Anticipators were supposed to be; eco-social basis, how important is the customers wills and needs to the owners and the level of modernism used in the gym. Spearman and multivariable regression test were used in this study. Amongst the factors introduced above the most important one came up to be; how modern are the facilities in the gym. Therefore, we suggest that managers use more modern facilities in their fitness centers in order to increase their customers.